PENGARUH KARAKTER EKSEKUTIF, KOMITE AUDIT, UKURAN PERUSAHAAN, LEVERAGE DAN SALES GROWTH PADA TAX AVOIDANCE - Swingly, Calvin; Sukartha, I Made (E-Jurnal Akuntansi, 2015)
ABSTRACT Tax avoidance is a tax savings actions that are still in the realm of tax law (lawful fashion). Executives character, audit committees, firms size, leverage and sales growth are used as independent variables were estimated impact on tax avoidance as the dependent variable and proxied through Cash Effective Tax Rate (CETR). This research was conducted on manufacturing firms in Indonesia Stock Exchange (IDX) 2011-2013. Data obtained by accessing the Indonesia Stock Exchange’s website. The samples in this study used nonprobability sampling method with purposive sampling technique in order to get a sample size of 41 companies and the number of observations is 123 times. Data in this study were analyzed with multiple linear analysis techniques. The results of this study indicate that the executives character and firms size has a positive effect on tax avoidance, while the negative effect of leverage on tax avoidance. Audit committee variables and sales growth has no effect on tax avoidance.
Keywords: tax avoidance, cash effective tax rate, executives character, manufacturing, indonesia stock exchange